Effect Of Solid Acids In The Conversion Of Glycerol Over Ru/Bentonite Catalyst In Glycerol Hydrogenolysis Reaction - Hamzah, Noraini; Alias, Aznira; Adnan, Nadia Farhana; Nadzri, Ainol Hayah; Mohamad Nordin, Norasikin; Kassim, Mohamad; Yarmo, Mohd Ambar (Journal of Science and Technology, 2010)
Glycerol known as by-product of transesterification of vegetables oil become an important materials after some chemical modification. In this study, hydrogenolysis reaction of glycerol to 1,2-propanediol was conducted using various supported ruthenium based catalyst. The support materials used in this study are bentonite ,TiO2, Al2O3 and SiO2. All experiments were carried out at reaction condition of 150°C, hydrogen pressure 20-30 bar for 7 hours and the 20%(wt) glycerol content in distilled water. The result shows that activity of the catalyts increased following this order: Ru/SiO2< Ru/TiO2 ≈ Ru/Al2O3 < Ru/bentonite. High selectivity to 1,2-propanediol was obtained in hydrogenolysis glycerol over Ru/TiO2 (83.7% ) and Ru/bentonite (80.1%) catalysts. Since Ru/bentonite catalyst performed better than other tested catalyst, we choose this catalyst system to investigate the effect of various solid acids (zeolite, ZrO2, Nb2O5 and amberlyst) on conversion of glycerol in hydrogenolysis reaction. Addition of solid acid in hydrogenolysis glycerol had promote the activity of Ru/bentonite catalyst drastically. The result shows that the presence of zeolite make the conversion of glycerol increased to maximum from 62.8% to 81.6% compared the other solid acids. Interestingly, selectivity to 1,2-propanediol still was achieved over 80.0%. These catalysts system were characterized by XRD, XPS, BET, and TEM for obtaining some physicochemical properties of the catalysts.